Impact sound of timber floors in sustainable buildings. (1st August 2017) - Caniato, Marco; Bettarello, Federica; Fausti, Patrizio; Ferluga, Alessio; Marsich, Lucia; Schmid, Chiara
Abstract: Timber buildings represent a robust alternative to traditional heavyweight constructions. They allow CO2 storage, high structure and performance reproducibility, fast assembly and final certification of every panel. Nowadays, acoustic insulation is one of the most requested performances on the part of inhabitants, but not always fulfilled. Since these kind of edifices are relatively new in the market, there are very few studies on acoustic properties, regarding on impact sound performances. In this paper, an in-depth analysis of impact noise on bare timber floors is presented, focusing on how impact sound reduction cannot be as efficient as in heavyweight constructions. Two new equations are proposed, modelling the impact sound pressure level of common bare timber structures and the influence of traditional floating floor systems is analysed. Highlights: The influence of the bare timber structures was analysed related to impact noise. Several in situ measurements of bare timber floors were performed. For crosslam bare floor a new frequency model is proposed for impact noise. For glulam bare floor a new frequency model is proposed for impact noise. A comparison with traditional heavyweight structures is provided.